Feasibility of ultrasound‐assisted catheter‐directed thrombolysis for submassive pulmonary embolism: A meta‐analysis of case series. (4th February 2020) - Wu, Jiayan; Chen, Haiming; Yu, Yongqin; Peng, Lingsheng; Li, Jieying; Liang, Hengrui; Ba, Manqing; Ruan, Honglian; Hong, Cheng
Abstract: Background: During the past few years, there has been a surge in the use of ultrasound‐assisted catheter‐directed thrombolysis (UACDT) for submassive pulmonary embolism (SPE). However, few studies evaluated the feasibility of UACDT for SPE. Purpose: To evaluate the feasibility of UACDT in treating SPE. Methods: A comprehensive search of online databases was performed. Search terms UACDT in SPE were entered into PubMed, Embase, Scopus and the Cochrane Library to identify related articles published until October 2018. A quality assessment and data extraction were performed by two researchers. Meta‐analysis was performed using R statistical software. Results: Twelve studies with 485 patients were included in this meta‐analysis. The pooled right ventricular/left ventricular ratio decrease and pulmonary artery systolic pressure drop after treatment was −0.34 (95% CI: −0.43, −0.25) and −15.05 (95% CI: −18.10, −12.00) mm Hg, respectively. The pooled major bleeding rate was 1.0% (95% CI: 0.0%, 3.0%), and the in‐hospital mortality was 0.0% (95% CI: 0.0%, 1.0%). Conclusion: This up to data meta‐analysis confirms that UACDT is a feasible treatment for SPE.